Construction of an attenuated glutamyl endopeptidase deletion strain of Nocardia seriolae. Issue 129 (October 2022) - Wang, Wenji; Hou, Suying; Chen, Jianlin; Xia, Liqun; Lu, Yishan
Abstract: The glutamyl endopeptidase homolog of Nocardia seriolae (GluNS) has been proved to be a potential virulence factor in our previous study. Present investigation was carried out to construct an attenuated N . seriolae strain by deletion with GluNS gene and evaluate its protective immunity in head snakehead. A deletion strain (NS-Δ GluNS ) was established by knockout of gene GluNS from wild strain N. seriolae ZJ0503 via homologous recombination. The LD50 of NS-Δ GluNS in 3.41 × 10 6 cfu/mL was significantly increased than that of wild strain in 4.75 × 10 5 cfu/mL, indicating that the virulence of N. seriolae has been attenuated with the knockout of GluNS . Meanwhile, applying NS-Δ GluNS as an attenuated live vaccine to immune hybrid snakehead, the non-specific immunity parameters (serum LYZ, POD, ACP, and AKP activities), specific antibody (IgM) titers production and immune-related genes ( MHCIα, CD4, and IL-8 ) expression were up-regulated in different tissues, which indicated that they were able to trigger humoral and cell-mediated immune responses. Furthermore, the protective efficacy in hybrid snakehead after vaccination with NS-Δ GluNS shown 73.53% relative percentage survival (RPS). Taken together, the attenuated NS-Δ GluNS was obtained successfully and it could elicit strong immune response and supply protective efficacy to hybrid snakehead against N . seriolae wild strain. Highlights: A deletion strain (NS-Δ GluNS ) was established from wild strain N. seriolae ZJ0503 . The virulence of N. seriolae has been attenuated with the knockout of gene GluNS. Attenuated deletion strain as live vaccines would be an effective strategy to control N. seriolae infection.